Mass Spectrometry Imaging of Cholesterol and Oxysterols - William Griffiths (Implication of Oxysterols and Phytosterols in Aging and Human Diseases, 2023)
Mass spectrometry imaging (MSI) is a new technique in the toolbox of the analytical biochemist. It allows the generation of a compound specific image from a tissue slice where a measure of compound abundance is given pixel by pixel, usually displayed on a colour scale. As mass spectra are recorded at each pixel the data can be interrogated to generate images of multiple different compounds all in the same experiment. Mass spectrometry (MS) requires ionisation of analytes but cholesterol and other neutral sterols tend to be poorly ionised by the techniques employed in most MSI experiments, so despite its high abundance in mammalian tissues cholesterol is poorly represented in the MSI literature. In this article we discuss some of the MSI studies where cholesterol has been imaged and introduce newer methods for its analysis by MSI. Disturbed cholesterol metabolism is linked to many disorders and the potential of MSI to study cholesterol, its precursors and its metabolites in animal models and from human biopsies will be discussed.